أثر التسويق بالعلاقات و التوجه نحو العملاء بالتطبيق علي بنك الخرطوم )2016م( - د.جعفرمحمدالحسنعثمان; د.هانيعوضعبداللهسليمان (White Nile Journal for Studies and Research, 2017)
The objective of the study was to identify the relationship between marketing relations and customer orientation in the Bank of Khartoum and determine its nature. The problem of research was to know the effect of marketing relations on customer orientation at Bank of Khartoum., The hypotheses of the study were based on one main hypothesis, which consisted of five sub-hypotheses, which examined the relationship. between the components of marketing relations (trust, commitment, communication, emotional bonding, honest promises) and their impact on customer orientation at Bank of Khartoum. The study was based on the historical approach, namely, the previous studies, the descriptive approach, the case study methodology, and the SPSS program to analyze the study data. The study reached a number of results, the most important of which are: The employees of the Bank of Khartoum deal transparently with customers. The employees of Khartoum Bank are committed to providing banking services that meet the requirements of the clients. A dedicated approach to customer relations, encouraging and increasing the commitment of the employees of the Bank of Khartoum to pay attention to the provision of banking services commensurate with the aspirations of customers and strengthen the bonds of trust between the client and the bank.